New records of euglenoid algae from Surma river in Bangladesh (Bangladesh Journal of Plant Taxonomy, 2023)
Eight species of Euglenophyceae from Surmariverin Bangladesh are reported in this paper. The species are: Euglena hyaline Klebs, E. robertilamii Lefèvre , Phacus gigas Da Cunha, P. pseudoplatalea Pochm., P. triqueter (Ehr.) Duj.var. oblonga Shi, Trachelomonas scabra Playf. var. labiata (Teiling) H.-P., Trachelomonas spiculifera Palmer, and T.umbili copora Conradare. After a careful review on the list of euglenoid algae of Bangladesh, all these eight species are found to be new addition, and hitherto described here for the first time in Bangladesh.Bangladesh J. Plant Taxon. 30(1): 107-110, 2023 (June)